PERFORMANCE OF A PROTOTYPE DRIFT CHAMBER WITH 100 MHZ FADC READOUT - Tkaczyk, S; Blissett, J; Hart, J; Hasell, D; Parham, A; Payne, B; Roberts, J; Saxon, D; Foster, B; Gilmore, R; Malos, J; Tapper, R; et al. (1988)
Rectangular drift chamber cells have been constructed and tested using an electron test beam facility at DESY. A systematic study of the time, spatial, energy and double track resolutions with a 100 MHz FADC readout is presented. The spatial resolution is 100 to 120 μm and the double track resolution is 2.5 mm with an Ar:C2H6 (50:50) gas mixture at atmospheric pressure. The dE dx resolution obtained corresponds to 6% resolution for a 72-layer chamber. © 1988.